Analysis of VOC Emission Characteristics in the Petrochemical Industry and Study on Fenceline Monitoring Techniques - Hyo Eun Lee; Seok J. Yoon; Jeong Hun Kim (Atmosphere)
Volatile organic compounds (VOCs) contribute to air pollution and pose health risks. This study investigates VOC emissions from petroleum refining and petrochemical industries using passive and active fenceline monitoring techniques. The primary objective of this research is to compare the characteristics and detection performance of passive and active sampling methods for VOC monitoring, particularly focusing on benzene and other major components, such as BTEX. A total of 87 VOC species were analyzed, with benzene, toluene, ethylbenzene, and xylene (BTEX) being dominant. Passive sampling detected benzene at an average concentration of 3.60 µg/m3, whereas active sampling recorded 1.33 µg/m3, showing up to 2.5 times higher values in passive sampling. In certain locations, benzene levels exceeded the EPA action level of 9 µg/m3, with a peak value of 18.37 µg/m3 at one sampling point. Meteorological conditions significantly influenced VOC concentrations, with stronger winds dispersing emissions more widely. This study provides crucial data for VOC emission control and regulatory policy development, emphasizing the need for continuous monitoring and targeted reduction strategies in industrial zones.